Economics of cooling cows to reduce seasonal variation in peak milk production - Kevin C. Dhuyvetter (Kansas Agricultural Experiment Station Research Reports, 2000)
The economic impact of cooling cows to reduce the seasonal variation in peak milk production was estimated using researchbased lactation curves and peak production numbers for a commercial dairy operation in Kansas. Reducing the seasonal drop in peak production that occurs in the late summer and fall months by 29% or more is profitable for second or higher lactation cows. This reduction represents an increase in total milk production over the entire lactation of slightly over 1% and an increase in the average annual peak production of only 1 lb. This indicates that achieving at least the breakeven level for second and higher lactation cows is a reasonable expectation. Based on the peak milk production for the farm considered in this analysis, it would not pay to cool first lactation cows, because their peak production was lower and exhibited very little seasonality. The economics of cooling cows is insensitive to feed prices, and only moderately sensitive to milk prices suggesting that the decision to cool dairy cows is basically independent of these factors. Although the benefit of cooling dairy cows, in terms of increased production, will depend on the type and effectiveness of the cooling system used, this analysis indicates that even small improvements in production can be economical.; Dairy Day, 2000, Kansas State University, Manhattan, KS, 2000;
Keywords: Dairy Day; 2000; Kansas Agricultural Experiment Station contribution; no. 01-166-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 861; Dairy; Economics; Heat stress; Cooling cows